Pengaruh Penggunaan Alat Peraga Benda Manipulatif Terhadap Hasil Belajar Matematika - Septi Asiatul Yulia; Sripatmi Sripatmi; Baidowi Baidowi (Griya Journal of Mathematics Education and Application, 2021)
This study is experimental using a post-test-only control design. This study aims to determine the effect of using manipulative object props on the learning outcomes of class VIII students of SMPN 2 Labuapi in the academic years 2018/2019. The sample of this study is class VIII-B as an experimental class, was given treatment with discovery learning models using manipulative object teaching aids with three meetings a learning process and VIII-C control class were given treatment using a direct learning model with three meetings learning process too. The instrument used in this study was a post-test in the form of description questions. Data analysis used polled variance t_test. Based on the research results, it was found that the experimental class 77.96 average value was greater than the control class of 71.03 where t_hit = 5.7 ≥ t_table = 2.0 with α =5%. From these results, there are differences in the learning process between the experimental and control classes. From these differences, it can be concluded that there is an effect of manipulative object props on the mathematics learning process of class VIII students of SMPN 2 Labuapi in academic years 2018/2019